Antinociceptive Activity of Ethanol Extract from Duguetia chrysocarpa Maas (Annonaceae). (3rd May 2012) - Almeida, Jackson Roberto Guedes da Silva; Araújo, Edigênia Cavalcante da Cruz; Ribeiro, Luciano Augusto de Araújo; de Lima, Julianeli Tolentino; Nunes, Xirley Pereira; Lúcio, Ana Sílvia Suassuna Carneiro; Agra, Maria de Fátima; Barbosa Filho, José Maria
Abstract : The ethanol extract from the fruits of Duguetia chrysocarpa was evaluated for its antinociceptive activity in chemical and thermal models of nociception in mice. The intraperitoneal administration of the ethanol extract (100, 200, and 400 mg/kg body weight) showed a dose-dependent inhibition of acetic-acid-induced abdominal writhes. The extract also produced a significant inhibition of both phases of the formalin test in all doses tested and increased the reaction time in hot-plate test at dose of 200 mg/kg. The data obtained suggest that the antinociceptive effect of the extract may be mediated via both peripheral and central mechanisms. The phytochemical investigation yielded the isolation of the benzenoid derivative 3-methoxy-4-ethoxy benzoic acid which is being reported for the first time in this genus.